Proceedings of ICT for Sustainability 2016 2016
DOI: 10.2991/ict4s-16.2016.4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing GHG Benefits Induced by ICT Services in Practice: A Case Study and Resulting Challenges

Abstract: High expectations are placed on the ability of ICT to play an important role in reducing GHG emissions, now and in the future. Several calculations of such benefits were put forward over the last years, usually performed by the industry. Their methods and assumptions, however, remained often unspecified, and the assessments frequently led to hardly plausible claims.In this paper, we present the results of applying a stricter approach to one specific service -the detection of gas leakages in the US through gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…As a result, there is a risk of increased use of generic data which in turn may add to contradicting results between LCAs [24]. Several data collection and calculation methods exist [5,11,32,33], which are known to be flawed [11,17,33,34] and the diverging usage of them could further increase the gap between the results, rendering them incomparable. Therefore, a better approach for measuring and collecting data in future studies needs to be identified.…”
Section: Challenge 2: Data Collection Methodsmentioning
confidence: 99%
“…As a result, there is a risk of increased use of generic data which in turn may add to contradicting results between LCAs [24]. Several data collection and calculation methods exist [5,11,32,33], which are known to be flawed [11,17,33,34] and the diverging usage of them could further increase the gap between the results, rendering them incomparable. Therefore, a better approach for measuring and collecting data in future studies needs to be identified.…”
Section: Challenge 2: Data Collection Methodsmentioning
confidence: 99%
“…Or challenging the idea that smart equals sustainable (Rivera [50]) or questioning where we should put our effort (Pargman [78]). Or assumptions that ICT is solution (Zapico [61], Walker [32]) or the central part of the solution (von Heland [45], Gui [34]), that net effect of ICT4S is always positive (Batchelor [74], Coroama [75]), or that responding to climate change is relatively simple Shabajee [31], easily calculated (Hankel [77]) or merely providing information to change behaviour Cakici [76].…”
Section: Humility and Desire To Learn Over Fixed Knowledge Setsmentioning
confidence: 99%
“…It may then be possible to estimate how much resources are saved indirectly by the push impacts. As the comparison baseline, however, is inherently hypothetical (i.e., how the world would have evolved without the pushed cleantech), any such estimate is subject to ontological uncertainty [38]. Further research is required to measure push impacts, as described below.…”
Section: Push Impacts Rebound and Technological Transitionmentioning
confidence: 99%